2015
DOI: 10.1002/2014ms000376
|View full text |Cite
|
Sign up to set email alerts
|

Second‐moment budgets in cloud topped boundary layers: A large‐eddy simulation study

Abstract: A detailed analysis of second-order moment budgets for cloud topped boundary layers (CTBLs) is performed using high-resolution large-eddy simulation (LES). Two CTBLs are simulated-one with trade wind shallow cumuli, and the other with nocturnal marine stratocumuli. Approximations to the ensemble-mean budgets of the Reynolds-stress components, of the fluxes of two quasi-conservative scalars, and of the scalar variances and covariance are computed by averaging the LES data over horizontal planes and over several… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 55 publications
3
43
0
Order By: Relevance
“…Cloudy boundary layers have been simulated using bulk cloud microphysics for cold-air outbreaks by Gryschka et al (2008) as well as for the analysis of second-order budgets in cloudtopped boundary layers for BOMEX and DYCOMS-II 10 (see Stevens et al, 2005) experiments by Heinze et al (2015). Recently, the embedded LCM has been employed for studying the effect of turbulence on the droplet dynamics and growth (Lee et al, 2014;Riechelmann et al, 2015), and for investigating the entrainment (of aerosols) at the edges of cumulus clouds (Hoffmann et al, 2015(Hoffmann et al, , 2014.…”
Section: Past and Current Research Fieldsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cloudy boundary layers have been simulated using bulk cloud microphysics for cold-air outbreaks by Gryschka et al (2008) as well as for the analysis of second-order budgets in cloudtopped boundary layers for BOMEX and DYCOMS-II 10 (see Stevens et al, 2005) experiments by Heinze et al (2015). Recently, the embedded LCM has been employed for studying the effect of turbulence on the droplet dynamics and growth (Lee et al, 2014;Riechelmann et al, 2015), and for investigating the entrainment (of aerosols) at the edges of cumulus clouds (Hoffmann et al, 2015(Hoffmann et al, , 2014.…”
Section: Past and Current Research Fieldsmentioning
confidence: 99%
“…Over the last 15 years, PALM has been applied for the simulation of a variety of boundary layers, ranging from heterogeneously heated convective boundary layers (e.g., Raasch and Harbusch, 2001;Letzel and Raasch, 2003;Maronga and Raasch, 2013), urban canopy flows (e.g., Park et al, 2012;Kanda et al, 2013), and cloudy boundary layers (e.g., Riechelmann et al, 2012;Hoffmann et al, 2015;Heinze et al, 2015). Moreover, it has been used for studies of the oceanic mixed layer (OML, e.g., Noh et al, 2010Noh et al, , 2011 and recently for studying the feedback between atmosphere and ocean by Esau (2014).…”
Section: Introductionmentioning
confidence: 99%
“…Typically, higher-order moments from LES are deduced from a spatial (horizontal) average (e.g., Heinze et al, 2015) as opposed to lidar measurements, which define turbulence as departure from a temporal mean. To account for this difference, variances from LES are shown in two different ways in Fig.…”
Section: Vertical Structurementioning
confidence: 99%
“…[], and Heinze et al . []. In the Reynolds‐stress budget, for example, the pressure terms act to redistribute the kinetic energy produced by shear and/or buoyancy between the velocity‐variance components, thus reducing the turbulence anisotropy generated by shear, buoyancy, and rotation.…”
Section: Introductionmentioning
confidence: 99%
“…Heinze et al . [, hereinafter H15] analyzed the second‐moment budgets in cloud‐topped boundary‐layer flows generated with LES and demonstrated that the pressure‐scrambling terms are of paramount importance in maintaining the Reynolds‐stress and the scalar‐flux budgets. A step forward is made in the present paper, where a detailed analysis of the pressure‐scrambling terms is performed.…”
Section: Introductionmentioning
confidence: 99%